Government and Foreign Entrepreneurs in the Soviet Economy of the 1920s – 1940s: Relations, Contradictions and Results - Taisiya V. Yudina (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. The article reveals motives of attracting foreign entrepreneurs to Soviet economy, difficulties with hiring local labor force in concessions, contradictions and solutions between Soviet organizations and concessioners. Relations between foreign entrepreneurs and Soviet government agencies as well as Soviet engineers and workers were regulated by the law.